Listening with Insomnia - Lacroix, Anabelle (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2023)
Insomnia is a disturbance of sleep, an “alarm bell”—or a signal to be listened to. This paper follows this signal to investigate what it means to “listen with insomnia” rather than against it (listening to fall asleep for future productivity). Through the analysis of the curatorial project Freedom of Sleep (21 April–16 May 2021), and my own experience of insomnia, which was the basis of the project, I develop a framework for listening with insomnia as a political practice. To this end, I draw on ideas of anxiety as a virtue and on the queer feminist theory of multi-level listening to positively reframe the common understanding of insomnia as an alarm bell. Rather than being seen as a depletion or a deficiency, “listening with insomnia” contributes to understanding insomnia as a resource, as an epistemology (a way of knowing).